IMPLEMENTATION OF THE RAD MODEL OF SOFTWARE APPLICATION FOR POPULATION DATA MANAGEMENT VILLAGE OF SUKAWENING BOGOR - Sismadi Sismadi (Kresnamedia Publisher, 2021)
Public administration services for the population are very important for management, safe data, good storage, easy search when needed. This condition has not been fulfilled if data management is done manually with large amounts of data. Sukawening village, located in the southern part of Bogor, experience this condition, the management of population data is done manually with the help of Microsoft Excel, which is an obstacle in realizing resident administrative services, including SKU, births, deaths, moving and arrival files. Solutions are needed to realize fast, efficient, and safe services for residents from lost and damaged conditions. The solution to the problem used in this research is to build an application system that is intended to manage population data. The system is built based on the web with the RAD model, a Codeigniter framework tool. With the realization of the application system, the management of population data in the Sukawening village is as expected.